(untitled) (Research, Society and Development, 2021)
Food allergy is an immunoreaction resulted by the ingestion of allergenic food by sensitive persons. It can result in less severe symptoms, like gastrointestinal and skin manifestations, but also can lead to great health hazardous as anaphylaxis. Once there is no cure to food allergies yet and the treatments available are not safe and effective enough, allergen avoidance is the more appropriate intervention. Therefore, allergic individuals rely on labelling information to make safer choices regarding food consumption. Because of this, many countries decided to establish mandatory declaration of major allergenic food within the label of pre-package food products. This work presents an analysis of the regulatory aspects of this theme in different countries. It was possible to evidence the evolution of regulatory requirements, although substantial differences are unfavorable to international trade and food safety.